Long-term Growth, Functional, and Aesthetic Outcomes after Fibula Free Flap Reconstruction for Mandibulectomy Performed in Children - Farooq Shahzad, MBBS, MS, FACS, FAAP; Peter W. Henderson, MD, MBA, FACS; Evan Matros, MD, MMSc, FACS; Peter G. Cordeiro, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. The long-term outcome of mandible reconstruction when performed in children has not been well documented. Methods:. This is a retrospective case series of patients who underwent immediate oncologic mandible reconstruction with a fibula free flap at younger than 18 years of age over a 20-year period, by a single surgeon, who had long-term follow-up. Results:. A total of 10 patients met inclusion criteria. Patient age ranged from 3 years and 8 months to 17 years and 9 months (mean 11 years). The etiology was malignant tumors in seven patients and benign locally aggressive tumors in three patients. All fibula flaps survived. All donor sites were closed primarily. The mean follow-up duration was 10 years and 5 months (range 3–20 years). The mean patient age at follow-up was 21 years and 10 months (range 8 years and 9 months to 30 years and 9 months). All patients achieved a regular diet and normal speech. Final occlusion was normal in seven of 10 patients. The aesthetic outcome, as evaluated by clinical examination, was a symmetric mandible in eight patients (in the other two the aesthetic asymmetry and malocclusion was minor and did not require operative intervention). Dental implants were ultimately placed in three patients. Leg function was normal in eight patients. Achilles lengthening and tendon transfer was required in one patient, and one patient developed ankle pain associated with running. Conclusion:. Mandible reconstruction in children with the fibula free flap provides excellent aesthetic and functional outcomes that are durable over time.